(untitled) (CAHIERS MAGELLANES-NS, 2024)
Indian women are coming up in all areas of life. . Despite progress, a very percent of women are taking a break in their professional lives to become full-time significant mothers and are not able to restart their career after a break period . As an Indian women ,it is a challenge to resume the career after the break as they are facing many obstacles. Perseverance and passion for long term goal is coined as Grit which is a powerful predictor of success and competence to reach one's goals .It is a positive and non-cognitive trait , powerful motivation to achieve.Grit trait against many challenging areas are researched over the years .This article is investigating the one of the most challenging area of women’s resumption of career against Grit. This article aim is to investigate grit trait score to the indian women who resuming their career and to determine the relationship between grit score and number of years career break taken.This article is based on original research among 210 working women among teachers from 6 schools and 2 colleges at Tambaram municipal area,chennai,India.The obtained data analysed descriptively and statistically which revealed that the women who resuming careers are grittier and no linear relationship in between resuming women’s grit trait score and their break period. No matter their break period, gritter women can resume their job though they have obstacle in resuming careers.